2018
DOI: 10.1111/exsy.12279
|View full text |Cite
|
Sign up to set email alerts
|

Processing technique of ratings for ranking of alternatives (PROTERRA)

Abstract: This paper presents a new approach to multicriteria decision analysis. They were named as processing technique of ratings for ranking of alternatives (PROTERRA). The consecutive steps of the process include normalization of the ratings, calculating of the ratings ratios within each pair of the alternatives, creating a component matrix for each of the criteria, and creating a total matrix that is the sum of the weighted component matrices. Aggregated ratings of individual alternatives result from the sums of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Step 5: Determine the relative closeness index to the ideal solution (C Ã i ). This can be obtained using Equation (23).…”
Section: Fuzzy Topsis Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 5: Determine the relative closeness index to the ideal solution (C Ã i ). This can be obtained using Equation (23).…”
Section: Fuzzy Topsis Approachmentioning
confidence: 99%
“…It was found that AISI A2 steel is best for the given application. Kobryn and Prystrom 23 presented a new approach to multi‐criteria decision analysis known as processing technique of ratings for ranking of alternatives. This method was used in choice of shopping center selection.…”
Section: Introductionmentioning
confidence: 99%
“…b) In some cases, the methods SAW and PROTERRA provided a slightly different assignment of the considered countries to a specific class of the innovation level. It may be assumed that this is the result, among other things, of the fact that the PROTERRA method reflects a disparity the values of the initial assessments for particular objects/options to a greater degree [as signaled by: Kobryń, Prystrom, 2018]. c) When comparing sets of countries assigned to each class level of innovation in the INPUTS and OUTPUTS, a proper correlation is not always visible.…”
Section: Analysis Of the Innovation Level In The European Union Countriesmentioning
confidence: 99%
“…In literature a wide variety of procedures and multicriteria methods of decision support are described. There are methods based on the f unctional model (the American school) and the relation model (the European school) [4][5][6]. In road planning, technologies such as GIS (Geographic Information System) are becoming increasingly popular [7][8][9][10], as well as methods using genetic algorithms [11].…”
Section: Introductionmentioning
confidence: 99%